Decrypting the influence of river classes on the effects on the environment through life cycle impact assessment (LCIA) of water treatment processes in Malaysia - Sharaai, Amir Hamzah; Mahmood, Noor Zalina; Sulaiman, Abdul Halim (American-Eurasian Network for Scientific Information, Jordan, 2010)
Parallel with the city development, industrial and commerce activities increase, river quality started to worsen with the occurrence of erosion, sedimentation and pollution. The scenario in Malaysia shows that the number of rivers in class I and II categories which is of high quality is falling fast but those in class IV and V categories are rising. This development is expected to be in line with the rapid progress experienced by this country along with the lack of awareness of the community in the efforts of preservation and conservation of the environment. The goal of this study is to see the extent of environmental impact form the water treatment processes which uses chemicals and electricity in varying quantum due to varying quality of the source water resulted from anthropogenic activities. To get the depiction of the damages, LCA method is used. Three different river classes is chosen, namely class I, class II and class III, as classified by Department of Environment, Malaysia. This study uses the ISO standards and Ecoindicator 99. In Ecoindicator 99, environmental damages are categorized into 3 types, namely, damage to Human Health, Ecosystem Quality and resources. This study is a streamlined LCA where only foreground data is needed namely the quantity of chemicals used during water treatment and electricity consumption. While the background data for the chemicals and electricity is acquired from Simapro and Jemai-LCA Pro software databases. LCI methodology was used for quantification of the impacts of portable water production at the different river classes. The data inventory is then classified and characterized with Ecoindicator 99 to identify the weaknesses of the system. Treatment of class III rivers contribute higher impact to the environment followed by class II rivers and the lowest impact is from class I river. The use of high quantity of chlorine was identified as the contributor to environmental impact. Weighting analysis shows that three main impact categories identified was respiratory inorganics, acidification/eutrophication and fossil fuels. The major chemical substance to respiratory inorganics and acidification/eutrophication impact categories are nitrogen oxides and sulphur oxides. Both substances are released during the production of Polyaluminium chloride (PAC) use as coagulant. While the material that contributes to fossil fuels impact are natural gas used for the generation of electricity. Â© 2010, INSInet Publication.